Identités professionnelles des formateurs d’enseignants d’EPS en UFR STAPS lors de l’année de préparation au CAPEPS - Youcef Alanbagi; Ghislain Carlier; Jacques Mikulovic (Recherches en Éducation)
Physical education and sport (PES) teachers’ training is historically marked by tensions between professional and academic guidance since the 1968’s creation of the STAPS spinneret and debates between theoretical and practical knowledge. This article focuses on the future PES teachers’ training of certificate of PES aptitude (CAPEPS) from the teachers’ trainers perspective. This research attempts to reveal a distribution of teachers’ trainers involved in the CAPEPS preparation year. It is based on a corpus of forty-one teachers’ trainers involved in the Sport science Masters’ degree, using a questionnaire and factorial correspondence analysis. The study shows three antagonists poles of these trainers (Scientists, Didacticians, Sportmen) and Sport science teachers’ trainers difficulties to represent their own position within the University. We also unveil that the PES beginning teacher picture for the teachers’ trainers, at the end of his degree course, is none other than that they think they have been. This research echoes the Peyronie studies (1998) showing the importance of the experiential dimension in identity construction, as Pérez-Roux in 2011 when she shows how about PES identity teacher’s construction is carried out.